2022
DOI: 10.3390/healthcare10071175
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Feedback for Arm Motor Function Rehabilitation after Stroke: A Randomized Controlled Trial

Abstract: A single-blind randomized controlled trial was conducted to compare whether the continuous visualization of a virtual teacher, during virtual reality rehabilitation, is more effective than the same treatment provided without a virtual teacher visualization, for the recovery of arm motor function after stroke. Teacher and no-teacher groups received the same amount of virtual reality therapy (i.e., 1 h/d, 5 dd/w, 4 ww) and an additional hour of conventional therapy. In the teacher group, specific feedback (“virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…The results of this study are in line with research (Salvalaggio et al, 2022) in stroke patients who were given virtual reality therapy, they experienced a change in their range of motion by 10 units (mean= 10; SD =1). This shows that the feedback received in VR therapy provides a significantly better motor training experience than in the real environment or in unsupervised conditions significantly (Salvalaggio et al, 2022).…”
Section: Figure 5 Forest Plot Of Range Of Motion Exercise On Range Of...supporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study are in line with research (Salvalaggio et al, 2022) in stroke patients who were given virtual reality therapy, they experienced a change in their range of motion by 10 units (mean= 10; SD =1). This shows that the feedback received in VR therapy provides a significantly better motor training experience than in the real environment or in unsupervised conditions significantly (Salvalaggio et al, 2022).…”
Section: Figure 5 Forest Plot Of Range Of Motion Exercise On Range Of...supporting
confidence: 87%
“…The results of this study are in line with research (Salvalaggio et al, 2022) in stroke patients who were given virtual reality therapy, they experienced a change in their range of motion by 10 units (mean= 10; SD =1). This shows that the feedback received in VR therapy provides a significantly better motor training experience than in the real environment or in unsupervised conditions significantly (Salvalaggio et al, 2022). The research conducted (Chen et al, 2022) also stated the same thing, where there was an increase in the range of motion of 4.72 units (mean= 4.72; SD= 0.87) in stroke patients who received virtual reality therapy.…”
Section: Figure 5 Forest Plot Of Range Of Motion Exercise On Range Of...supporting
confidence: 87%
“…Technologies for the UL consisted of Virtual Reality Rehabilitation System (VRRS, Khymeia Group Ltd. Noventa Padovana, Italy), with a computer-based tasks displayed in a virtual scenario. Patients were asked to emulate real arm movements, via a motion tracking system controlling a virtual object [8]. For patients who could benefit from treatments with a robotic device, AMADEO (Tyromotion GmbH, Graz, Austria) was used, an end-effector robot allowing to perform selective voluntary movements of the hand and fingers, controlled by surface electromyography (sEMG) detected from fingers flexors and extensors muscles [19].…”
Section: Technology Devicesmentioning
confidence: 99%
“…Recently, a trial aimed to assess maintenance of rehabilitation clinical effects at 6-months follow-up, found that improvements were preserved in patients receiving treatment at least 6 h per day, for three consecutive weeks, even in the chronic phase after stroke [7]. Furthermore, a combination of conventional therapy (CT) and virtual reality (VR) for at least 40 h of rehabilitation was found to enhance clinically relevant improvement in UL motor function, in chronic stroke patients [8]. However, it is not yet known which are the clinical features (e.g., neurological profile; clinical history; level of motor, language, and cognitive functions at baseline) allowing clinicians to predict the recovery potential of a patient before rehabilitation, also considering the treatment pathways followed within the National Health System.…”
Section: Introductionmentioning
confidence: 99%
“…Although recently there has been increasing interest in some crucial aspects of rehabilitation intervention such as the optimal feedback to be provided ( 7 , 8 ), most of the interventions proposed in the last decades came from the pragmatic application of new evidence from different fields of knowledge. An example is the tremendous impact that neurophysiological advancements in the study of neural plasticity have had in the field of rehabilitation after stroke ( 3 ).…”
Section: Introductionmentioning
confidence: 99%